Encyclopaedia Britannica 2004 ultimate reference suite. - Encyclopaedia Britannica Australia (Australia Encyclopaedia Britannica, 2004)
Contains Encyclopaedia Britannica, Britannica Student Encyclopedia, and Britannica Elementary Encyclopedia, 101,000 articles, 300,000 dictionary entries, 500,000 thesaurus entries, a world atlas, 2,775 maps and 25,000 images and multimedia.
Disc 1: Installation -- disc 2: Articles -- disc 3: Images -- disc 4: Multimedia -- disc 5: Multimedia -- disc 6: Multimedia.
Keywords: Electronic encyclopedias; Encyclopedias and dictionaries